PENGARUH MODEL DISCOVERY LEARNING MELALUI PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR DAN MINAT BELAJAR FISIKA SISWA PADA KONSEP FLUIDA STATIS DI SMAN 8 REJANG LEBONG - Indah Cahya Purnamasari; Eko Swistoro; Desy Hanisa Putri (UNIB Press, 2017)
The aims of research are (1) to find the effect of learning with discovery learning model through a scientific approach to students’ learning outcomes, (2) to find the effect of learning to students’ learning interest, and (3) to describe the improvement of students' learning outcomes.This type of research is quasi experiment. The sample was taken by using purposive sampling technique to determine class XI IPA 2 as experimental class and class XI IPA 1 as control class. The data were analysed by using t-test with two independent samples. The results show that there is significant influence of the use of Discovery Learning model through scientific approach to learning outcomes (tcount 2.64> ttable 1.68) and student learning interest (tcount 3.95 > ttable 1.68). The improvement of students' learning outcome in experimental class is higher than the improvement of the control class learning result (0.68 > 0.64). It is concluded that there is a significant influence of the use of Discovery Learning model through scientific approach to student learning outcomes and to students’ learning interest. Keywords: Learning Outcomes, Learning Interests, Discovery Learning Model, Scientific Approach.